A randomised controlled trial of guided internet-based cognitive behavioural therapy for perfectionism: Effects on psychopathology and transdiagnostic processes. (September 2019) - Kothari, Radha; Barker, Chris; Pistrang, Nancy; Rozental, Alexander; Egan, Sarah; Wade, Tracey; Allcott-Watson, Hannah; Andersson, Gerhard; Shafran, Roz
Abstract: Background and objectives: Perfectionism is a transdiagnostic process that has been associated with a range of psychopathology and also with other transdiagnostic processes. We have previously shown that guided internet-based cognitive behavioural therapy (ICBT) can reduce symptoms of dysfunctional perfectionism, however, no impact was observed on symptoms of depression and anxiety. Here we explore the impact of guided ICBT for perfectionism on symptoms of other associated psychopathology, specifically obsessive-compulsive disorder (OCD) and eating disorders, and also on other associated transdiagnostic processes (self-esteem, intolerance of uncertainty, and self-compassion). Methods: Participants who presented with clinical levels of perfectionism were randomised to an experimental group that received the intervention (n = 62), or a wait list control group (n = 58). Questionnaires assessing symptoms of OCD, eating disorders, self-esteem, intolerance of uncertainty, and fear of self-compassion were completed pre-intervention, post-intervention (12 weeks), and at follow-up (24 weeks). Between group effect sizes are reported. Results: The intervention led to significant decreases in symptoms of OCD ( d  = −0.9; CI: -1.4, −0.4) and eating disorders ( d  = −0.6; CI: -1.0, −0.1), and had an impact on other transdiagnostic processes resulting in increased self-esteem ( d  = 0.7; CI: 0.2, 1.2), decreases in intolerance of uncertainty ( d  = −0.9; CI: -1.4, −0.4), and fear of self-compassion ( d  = −0.8; CI: -1.3, −0.3). At follow-up changes were maintained in symptoms of OCD ( d  = −1.3; CI: -1.8, −0.8), disordered eating ( d  = −0.7; CI: -1.2, −0.2), intolerance of uncertainty ( d  = −0.8; CI: -1.2, −0.3), and fear of self-compassion ( d  = −1.0; CI: -1.5, −0.5). Conclusions: Guided ICBT for perfectionism improves associated psychopathology and transdiagnostic processes. ClinicalTrials.gov registration no. NCT02756871. Highlights: Internet based CBT for perfectionism led to decreases in symptoms of obsessive-compulsive disorder and eating disorders. The intervention resulted in increased self-esteem, and decreases in intolerance of uncertainty and fear of self-compassion. Decreases in symptoms of obsessive-compulsive disorder and eating disorders were maintained at 24-week follow-up. Decreases in intolerance of uncertainty and fear of self-compassion were also maintained at 24-week follow-up.